SYSTEMS TO INTELLIGENT AUTOMATION (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This study explores the profound impact of artificial intelligence on industrial automation and focuses on the revolution of autonomous systems. A detailed literature study shows major improvements in AI technologies such as machine learning, computer vision, and natural language processing that improve the capabilities of robotic systems. Key approaches used in diverse studies include integrating AI with legacy systems, making real-time decisions, and developing intelligent robotic systems. Data quality issues, integration with current infrastructures, and the challenges of human-robot collaboration are all rigorously examined, as are the ethical considerations and security risks that come with the introduction of AI-driven technology. The findings emphasize the importance of addressing operational challenges in order to fully benefit from AI-enabled automation, paving the way for a more sustainable and efficient industrial landscape.